A Day in the Life of the American Woman: Construction and Mediation of the “American Woman” in Photographic Essays - Jane Bayly (Transatlantica)
In 2005, fifty women photographers participated in a project to capture the everyday lives of over seventy American women on the same day in order to provide a composite portrait of the modern American woman in the twenty-first century. Through a close analysis of the photographs and accompanying texts this article questions to what extent the definition proposed by the book A Day in the Life of the American Woman remains faithful to a “traditional” vision of the American woman, or on the contrary to what extent this definition reflects an empowered and diversified vision of women since the 70s feminist movement. Our findings reveal that although A Day in the Life presents a diversified vision of the modern, American woman, it simultaneously remains faithful to a more stereotypical vision where a woman’s primary goal is to remain a mom.